Assessment of peri-device leaks after interventional left atrial appendage closure using standardized imaging by cardiac computed tomography angiography - Lindner, Simon; Behnes, Michael; Wenke, Annika; Sartorius, Benjamin; Ansari, Uzair; Akın, Muharrem; Mashayekhi, Kambis; Vogler, Nils; Haubenreisser, Holger; Schönberg, Stefan; Borggrefe, Martin; Akın, Ibrahim (The international journal of cardiovascular imaging, 2019)
Cardiac computed tomography angiography (cCTA) has recently been proposed for evaluation of successful interventional left atrial appendage closure (LAA/LAAC). This prospective longitudinal observational study aims to assess this proposal by applying a standardized imaging protocol to detect and quantify peri-device leaks (PDL) after LAAC. cCTA datasets of consecutive patients 6 months after successful LAAC were acquired on a third generation dual-source computed tomography system and reconstructed with a slice thickness of 0.5 mm. The standardized multi-planar reconstruction LAA occluder view for post-implantation evaluation (LOVE) algorithm was used to assess PDL in relation to LAA morphology and implanted LAAC devices. A total of 49 patients (median age 80 years, 24% female) were included consecutively. Overall PDL rate was 31%. Leak rates among different left atrial appendage morphologies varied largely. Windsock type had the highest incidence of PDL (47%). AMPLATZER™ AMULET™ device type revealed slightly higher PDL rates than WATCHMAN™ type and showed larger leaks. However, no statistical differences were found. PDL can be sized best in LOVE sagittal views, whereas a synopsis of LOVE sagittal, axial and coronal views allows further examination and detection of small leaks. PDL are common after successful interventional LAAC, which can be accurately detected and sized by standardized cCTA imaging protocols.